Trackways of the American Crocodile (Crocodylus acutus) in Northwestern Costa Rica: Implications for Crocodylian Ichnology. Issue 1 (2nd January 2018) - Farlow, James O.; Robinson, Nathan J.; Kumagai, Cory J.; Paladino, Frank V.; Falkingham, Peter L.; Elsey, Ruth M.; Martin, Anthony J.
ABSTRACT: We documented trackways of free-living Crocodylus acutus on beaches at the mouths of Tamarindo and Ventanas estuaries, Costa Rica. Our crocodiles had estimated total lengths of 1–3 meters or more. Manus prints have five digits, with digits I–III bearing claw marks. Pes prints have four digits, with claw marks on digits I–III. The pes is plantigrade. Claws generally dig into the substrate. Apart from claw marks, digit I and the heel of the pes are usually the most deeply impressed parts of footprints. Trackways are wide-gauge. Pes prints are usually positioned just behind ipsilateral manus prints of the same set and may overlap them. Manus and pes prints angle slightly outward with respect to the crocodile's direction of movement. Claw-bearing digits of both the manus and pes may create curved, concave-toward-the-midline drag marks as the autopodium is protracted. The tail mark varies in depth and clarity, and in shape from nearly linear to markedly sinuous. Sometimes the tail mark hugs the trackway midline, but sometimes it is closer to, or even cuts across, prints of one side. American crocodile footprints and trackways are similar to those observed in other extant crocodylian species, indicating substantial trackway conservatism across the group.